2010
DOI: 10.4103/0970-9290.66646
|View full text |Cite
|
Sign up to set email alerts
|

Role of genes in oro-dental diseases

Abstract: In oral cavity, the spectrum of diseases due to genetic alterations ranges from developmental disturbances of teeth to the pre-cancerous and cancerous lesions. Of late, significant progress has been made in the molecular analysis of tumors. With molecular genetic testing emerging as diagnostic, prognostic, and therapeutic approach, a review of genetic alterations ranging from the development of oro-facial structures to the tumors in the head and neck region are addressed in this article. The functional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 1 publication
0
13
1
5
Order By: Relevance
“…To date, only mutations in the MSX1 and PAX9 genes seem to be tooth‐type specific. The phenotype–genotype correlation analyses demonstrated that the MSX1 mutations are associated with hypodontia that predominantly affects second premolars and third molars, whereas mutations in PAX9 lead to agenesis of most molars, which can sometimes be combined with the absence of other teeth, including second premolars (Kavitha, Priyadharshini, Sivapathasundharam, & Saraswathi, ; Matalova, Fleischmannova, Sharpe, & Tucker, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only mutations in the MSX1 and PAX9 genes seem to be tooth‐type specific. The phenotype–genotype correlation analyses demonstrated that the MSX1 mutations are associated with hypodontia that predominantly affects second premolars and third molars, whereas mutations in PAX9 lead to agenesis of most molars, which can sometimes be combined with the absence of other teeth, including second premolars (Kavitha, Priyadharshini, Sivapathasundharam, & Saraswathi, ; Matalova, Fleischmannova, Sharpe, & Tucker, ).…”
Section: Discussionmentioning
confidence: 99%
“…These nucleotide variations, regardless of the pathogenic mechanism(s) involved, probably lead to inactivation of one PAX9 gene allele, suggesting haploinsufficiency as the potential underlying cause of tooth agenesis in affected individuals. It has been shown that a reduced amount of the PAX9 protein specifically affects molar development (7,15). However, the specific pattern of tooth agenesis associated with PAX9 mutations has not been Table 2 Paired box 9 (PAX9) mutations identified in patients with permanent tooth agenesis UTR, untranslated region.…”
Section: Discussionmentioning
confidence: 99%
“…At this critical stage of odontogenesis, Pax9 is required to maintain the mesenchymal expression of bone morphogenetic protein 4 ( Bmp4 ), which is involved in the induction of the epithelial signalling centre for tooth morphogenesis (enamel knot) . Analysis of human phenotypes revealed that PAX9 mutations are dominantly associated with the absence of most molars, which can sometimes be combined with the absence of second premolars and some of the incisors . Common PAX9 polymorphisms have been shown to be significantly correlated with hypodontia, including third‐molar agenesis, as well as with the crown size and shape of permanent teeth in East Asian populations .…”
mentioning
confidence: 99%
“…Craniofacial research is currently focused especially on determination of genotypes of different syndromes [6, 1821]. …”
Section: Part 1: Definition Of Syndromesmentioning
confidence: 99%